0005 Efficacy of SM-1 in a Transient Insomnia Model. (27th April 2018) - Dahl, T; Roth, T; Zammit, G; Ahmad, M; Chen, L
Abstract: Introduction: The 1983 National Institutes of Health Consensus Conference distinguished between transient and chronic insomnia. They stated " Transient insomnia refers to insomnia related to situational stress. The most frequent use of hypnotics is for short-term use. Despite this, transient insomnia has not been systematically studied in clinical trials. Hence the safe and effective treatment for transient insomnia represents an unmet need. This study assessed the effects of SM-1 vs. Placebo on PSG-defined Total Sleep Time (TST) in a 5-hour phase advance model of transient insomnia. Methods: This was a randomized, double-blind, three-way cross-over study assessing the efficacy of a single dose of SM-1 (50 mg diphenhydramine, 5 mg delayed-release zolpidem and 0.5 mg delayed-release lorazepam) versus an active comparator (5 mg delayed-release zolpidem and 0.5 mg delayed-release lorazepam) and placebo after a 5-hour phase advance in healthy subjects reporting a past history of transient insomnia. Subjects slept in the laboratory for 8 hours having gone to bed 5 hours before their habitual bedtime on each of the 3 treatment days. Upon awakening subjects filled out a post-sleep questionnaire. Results: Mean TST treatment with SM-1 was 382.9 minutes, an increase 126.7 minutes over placebo (256.2 minutes; p<0.001). When broken out by quarters of the night, SM-1 was had greater TST than placebo during each quarter (p=0.006). Mean TST following treatment with SM-1 also showed an increase of 43.7 minutes over the Comparator (339.2 minutes; p=0.014). SM-1 reduced wakefulness after sleep onset (WASO) by 106.4 minutes compared with placebo (75.8 minutes with SM-1 compared with 182.2 for placebo; p<0.001). SM-1 reduced WASO by 32.8 minutes compared with the Comparator (108.6 minutes; p=0.067). Mean LPS was numerically shortest for SM-1, followed by Comparator and then Placebo (31.2, 42.1 and 50.1 minutes, respectively) although no comparison achieved statistical significance. Differences between treatments in the total number of awakenings (NAW) were not statistically significant. On a post-sleep questionnaire subjects reported their mean total sleep time was increased by 79.3 minutes for SM-1 compared to placebo (445.2 vs 365.9 minutes; p<0.001). Conclusion: Support (If Any):